The games were coming - Anthony, Michael . (Heineman., 1963)
Set in Michael Anthony's homeland - Trinidad - and written in his trademark simple yet elegant style, this coming of age story has it all: ambition, love and the loss of innocence - all of the angst of that transition to young adulthood, as relevant today as it was when the novel was first published in 1963.